(untitled) (Research, Society and Development, 2023)
Rice (Oryza sativa L.) is a staple food worldwide for around 2.5 billion people and the demand for it is expected to double by 2050. The objective of the work was to evaluate the asepsis process, identify the pathogens present in the BRS A706 CL and BRS Pampeira cultivars and understand how this practice influences seed quality. The experiment was conducted at the Phytopathology Laboratory of the Federal University of Tocantins - UFT, Campus Gurupi, and consisted of carrying out seed health through the "bloter test" filter paper test, in which 100 seeds of each cultivar were divided into eight sterilized plastic boxes, containing 25 seeds each, totaling 200 seeds. The structures in the seeds were identified by observation using a stereoscopic magnifying glass and an optical microscope, comparing them with reference figures. The data obtained was subjected to the average test in Excel software and presented in column and pie charts, highlighting the most frequent pathogens in the cultivars evaluated. Curvularia, Alternaria, Bipolaris and Fusarium were the most frequent genera in rice seeds. It was concluded that seed processing is not sufficient to reduce the infestation of pathogenic fungi, and seed treatment is recommended to reduce the effects of these pathogens.